Optimalisasi Produktivitas Alat Gali Muat dan Alat Angkut Menggunakan Metode Quality Control Circle (QCC) untuk Mencapai Target Produksi Batu Andesit pada PT. Pebana Adi Sarana - Angga Saputra; Ahmad Fadhly; Hisni Rahmi; Zella Navtalia; Diah Wully Agustine (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
PT. Pebana Adi Sarana targets monthly production operations of 20,000 tons/month while actual production is only around 15,000 tons/month, which means that the production target has not been achieved. The factors that cause the failure to achieve the production operation target can be due to ineffective equipment performance, Low equipment performance is one of the things that cause production not to be achieved, so it needs to be studied. The purpose of the study to be achieved is to analyze the actual productivity of loading and unloading equipment and transportation equipment after repairs and conduct improvement analysis using the Quality Control Circle (QCC) method. The data taken for the research is in the form of Excavator and dump truck cycle time data, effective working time, tool specifications. The actual productivity of loading and unloading equipment and transportation equipment at PT. Pebana Adi Sarana for dump trucks of 19,146 tons/month. trucks are 16,351 tons/month while for the Quality Control Circle (QCC) method. The company only needs to carry out the number of tools needed for 3 units of Scania p380 dump trucks and 1 unit of komatsu PC 300 excavator with a production of 21,295 tons/month has exceeded the production target set by the company.